Telecontrolling Smart Fish Feeder Berbasis Mikrokontroler Dan Aplikasi Android - Prayogo Khanua Almufaridz; Mila Kusumawardani; Rachmad Saptono (Jurnal Jaringan Telekomunikasi, 2021)
Indonesia is a country known for its aquaculture. Regular feeding is influential in a good farming management system to obtain quality fish. However, the feeding system is still oriented to human resources that are still manual, resulting in an erratic feeding schedule and size, making it different for each feeding. Feeding planning must be precise so that fish growth is fast. In this research, an automatic fish feeder called "smart fish feeder" was made. This tool uses a microcontroller-based control system that is connected to the internet and an android application. In the control system circuit using the Arduino Uno connected to the ESP32 to be connected to the internet, there are also several actuator and sensor components. The control system gets input to adjust the smart fish feeder device through a smartphone with the smart fish feeder application installed. Based on the results of the tests carried out, for the ultrasonic sensor, the average error value is 6, the error percentage is 0.896%, and the accuracy is 99.104% with a measurement distance of 5-25cm. The loadcell sensor obtained an average error value of 2.8, a percentage error of 0.067%, and an accuracy of 99.933%.